Ecoconsciousness Versus Egoconsciousness: An Ecocritical Reading of GM Hopkins’ “God’s Grandeur” and William Stafford’s “Travelling through the Dark” - Dhungel, Nabaraj; Thapa, Kalpana (Humanities and Social Sciences Journal, 2021)
This article explores how the poets G M Hopkins and William Stafford attempt to present the conflict between egoconsciousness and ecoconsciousness in their poems “God’s Grandeur” and “Travelling through the Dark” respectively. It also endeavours to find out their strategy and mission of exposing the superiority complex of the humans guided by anthropocentrism and highlighting the significance of ecocentrism necessary for creating balance in ecosystem and human lives. This paper assertively justifies that the poets, through their poems, depict the humans as problems and nature as solution of all problems due to its opposite qualities and the quality of timelessness and spacelessness. To justify the argument, ideas and notions of ecocritics Timothy Clark, Bill Devall and Stan Rowe have been brought as references. Mainly, this research work attempts to excavate and publicize how the writers make ecocritical discourse in demolishing, transforming and raising ecoconsciousness within the people (readers) for environmental preservation and conservation of lives. It is found that the poets effort to transform human minds, attitudes and behavioural practices from egocentric to ecocentric.